Perilaku Komunikasi Pemujaan pada Fandom Idol Korea dalam Komunitas EXO-L Samarinda - Linda Ayu Lestari; Kadek Dristiana Dwivayani; Harry Isra Muhammad; Ziya Ibrizah (Institut Nalanda, 2026)
The Korean Wave (Hallyu) phenomenon has significantly influenced Indonesian popular culture, including the emergence of fan communities or fandoms. One of the major fandoms that has developed is EXO-L, the fan community of the Korean idol group EXO. This study aims to describe the idolization behavior that occurs within the EXO-L Samarinda community, as well as the factors that drive it and its impact on fans' lives. This study uses Henry Jenkins' fandom theory and uses a qualitative descriptive method with a phenomenological approach. Data were obtained through observation, in-depth interviews with four informants who are members of the EXO-L Samarinda community, and documentation of community activities both online and offline. The results show that the idolization behavior of EXO-L Samarinda members is formed through three stages of celebrity workshop, namely entertainment-social, intense-personal, and borderline-pathological. This behavior is manifested through intensive discussions about idols, strong emotional bonds, and consumptive actions such as purchasing merchandise and the desire to attend concerts abroad. The main factors driving idolization behavior include interest in EXO's music and visuals, the influence of the social environment, and the role of social media in forming intense interactions. The positive impacts of this behavior include the formation of solidarity and personal motivation, while the negative impacts include consumerism, emotional dependence, and the emergence of excessive fanaticism. This research is expected to contribute to the study of communication science, particularly in understanding the phenomenon of fandom and worship behavior in the digital media era.